2010
DOI: 10.4012/dmj.2009-079
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sintering temperature on physical and compositional properties of α-tricalcium phosphate foam

Abstract: Effects of sintering temperature on the physical and compositional properties of α-TCP foam fabricated using the polyurethane foam method were examined. When a polyurethane foam coated with α-TCP slurry was sintered at 1,400-1,550°C, α-TCP foam having basically the same fully interconnected porous structure was produced although shrinkage occurred with increasing sintering temperature. On porosity of the α-TCP foam, a higher foam porosity of 95% was obtained when sintered at 1,400°C as compared to the 90% poro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…As the sintering temperature was raised, the porosity decreases but not significantly. These result are in agreement with a study by Udoh et al [10] who reported that TCP porosity decreases from 95 to 90% with increasing sintering temperature from 1450 to 1550˚C. A tendency of decrease in porosity with increase in sintering temperature might arise from the fact that when sintering temperature increases, densification rate of particles escalates to form a denser structure with fewer pores.…”
Section: Fig 2 the Effect Of Stirring Time On Porosity Of Samples Asupporting
confidence: 93%
“…As the sintering temperature was raised, the porosity decreases but not significantly. These result are in agreement with a study by Udoh et al [10] who reported that TCP porosity decreases from 95 to 90% with increasing sintering temperature from 1450 to 1550˚C. A tendency of decrease in porosity with increase in sintering temperature might arise from the fact that when sintering temperature increases, densification rate of particles escalates to form a denser structure with fewer pores.…”
Section: Fig 2 the Effect Of Stirring Time On Porosity Of Samples Asupporting
confidence: 93%
“…Increasing of the interconnected pores supports extensive vascularization, rapid bone regeneration and good osteointegration [14][15][16][17][18][19] . It should be mentioned that porosity and mechanical strength have a trade-off relationship [20][21][22] . Therefore optimization of the porosity and mechanical strength is important for the clinical use of porous CO 3 Ap.…”
Section: Discussionmentioning
confidence: 99%
“…After measuring the area of the foams using a digital micrometer (IP65, Mitutoyo Co., Ltd, Kanagawa, Japan), each specimen was crashed vertically with a load cell at a crosshead speed of 1 mm/min [6,8,[17][18][19][20][21] using a table-mount universal testing machine (Autograph AGS-J, Shimadzu Corp., Kyoto, Japan). For each group, 8 specimens were tested to determine the average compressive strength value.…”
Section: Characterizationmentioning
confidence: 99%
“…CO 3 Ap foam, which approximated the fully interconnecting structure and inorganic composition of the bone, was fabricated based on dissolution-precipitation reaction using fully interconnecting porous precursor [6,7]. For example, alpha tricalcium phosphate (αTCP) foam was fabricated as a precursor using the reticulated foam replication method [8]. Then, the precursor αTCP foam was immersed in carbonate salt solution to transform its composition into CO 3 Ap based on dissolution-precipitation reaction without changing its interconnecting porous structures.…”
Section: Introductionmentioning
confidence: 99%